An integrated swimming monitoring system for the biomechanical analysis of swimming strokes - James, D. A.; Leadbetter, R. I.; Neeli, M. R.; Burkett, B. J.; Thiel, D. V.; Lee, J. B. (Sports Technology, 2011)
This paper describes the development of a complete wearable swimming system for performance analysis, together with a sample application. The system comprises wearable nodes, data processing tools in MATLAB and integration with video. The swimming nodes are small in size and designed to be worn on body segments of interest, typically lower leg, lower arm, and the sacral or cervical regions. Each node contains inertial sensors, screen, data storage and RF communications for synchronisation and data download. The device is controlled using a microcontroller with a scheduler-based operating system to conserve power and is custom-packaged with a user interface and USB port that is fully waterproof. The cost of manufacture is a few hundred dollars in small-run quantities. The developed analysis software builds upon previously developed tools, can communicate with the nodes individually and can synchronise the recording of multiple units through a custom-developed protocol. Video is integrated into the developed tools as a method of presenting the sensor data alongside a more traditional analysis tool. A case study of the system analyses swim stroke phase with video and demonstrates the utility of the system as a tool for temporal stroke phase identification in the high-performance environment.